OPTIMIZATION OF GAMIS PRODUCT INVENTORY MANAGEMENT ATTWENTY2 CLOTHING STORE - Nadila Faiza; Nurul Hidayati (Universitas Kuningan, 2025)
Twenty2 Clothing Store is a fashion business experiencing difficulties in inventory control due to demand uncertainty. The research was conducted from January to September 2025 at Twenty2 Clothing Store. The methods used were demand forecasting, probabilistic inventory modeling, and analysis according to the Committee of Sponsoring Organizations of the Treadway Commission (COSO). The study's results indicated that the most appropriate forecasting method was Holt-Winters exponential smoothing. The amount of safety stock needed from June 2025 to January 2026 was 129 pcs, from February to March 2026 was 112 pcs, and from April to May 2026 was 35 pcs. The reorder point for June 2025-January 2026 was 131 pcs, for February-March 2026 was 134 pcs, and for April-May 2026 was 38 pcs. The recommended optimal order quantity for June 2025-January 2026 was 396 pieces, for February-March 2026 was 176 pieces, and for April-May 2026 was 28 pieces. The analysis of inventory management internal control according to COSO control components at Twenty2 Clothing Store was good but still simple and not yet digitalized. Therefore, Twenty2 Clothing Store can use the forecasting results and improve internal control in a systematic, structured, and recorded manner with a digitalization system.